Analytical Study and Design of Flexible Pavement (Global Journals of Research in Engineering, 2022)
Flexible pavement usually constructed of bituminous materials such that they remain in contact with the underlying material even when minor Distortions occur Flexible pavement usually consists of a bituminous surface underlaid with a layer of granular material and a layer of a suitable mixture of coarse and fine materials Flexible pavement is the pavement that remains adjacent to the surface soil road even if the surface is rutting Provides sufficient thickness for load distribution through a multilayer structure so that the stresses and strains in the Subgrade soil layers are within required limits The strength of subgrade soil would have a direct bearing on the total thickness of the flexible pavement
Keywords: flexible design; pavement; asphalt design